2019
DOI: 10.1186/s12984-019-0581-1
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the target area: an integrative view of tDCS-induced motor cortex modulation in patients and athletes

Abstract: Transcranial Direct Current Stimulation (tDCS) is a non-invasive technique used to modulate neural tissue. Neuromodulation apparently improves cognitive functions in several neurologic diseases treatment and sports performance. In this study, we present a comprehensive, integrative review of tDCS for motor rehabilitation and motor learning in healthy individuals, athletes and multiple neurologic and neuropsychiatric conditions. We also report on neuromodulation mechanisms, main applications, current knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 392 publications
(504 reference statements)
3
96
0
3
Order By: Relevance
“…Traditional tDCS, while a promising therapeutic strategy, utilizes relatively large sponge electrodes that generate diffuse electric fields. This leads to relatively high inter-subject variance in cortical target engagement and tDCS-induced functional improvements [ 16 ]. High-definition tDCS (HD-tDCS) is a relatively new technique that uses small gel-based electrodes in combination with neuro-modeling to optimize and better control tDCS-induced electric fields [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional tDCS, while a promising therapeutic strategy, utilizes relatively large sponge electrodes that generate diffuse electric fields. This leads to relatively high inter-subject variance in cortical target engagement and tDCS-induced functional improvements [ 16 ]. High-definition tDCS (HD-tDCS) is a relatively new technique that uses small gel-based electrodes in combination with neuro-modeling to optimize and better control tDCS-induced electric fields [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal symptoms in COVID-19 are probably a consequence of systemic inflammation, but a key factor to be addressed, as the musculoskeletal system is strongly related to the capacity to move and perform daily life activities, and probably should be addressed early in the treatment of infected patients. Non-invasive neuromodulation techniques could not only reduce the muscle symptoms present in this population but also improve respiratory muscle function ( 175 178 ), training ( 44 , 179 181 ), and fatigue ( 182 ), increasing their motivation, and likely positively affecting the cognitive process, which could aid them in the recovery from the illness.…”
Section: Methodsmentioning
confidence: 99%
“…These techniques can be used in the management of psychiatric symptoms associated with the COVID-19 pandemic ( 39 , 42 , 43 ). Non-invasive neuromodulation has also shown to be a potent resource in cognitive and physical rehabilitation ( 44 , 45 ) and could serve additional goals in the management of COVID-19 patients ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…M1 encompasses much more than movement organization, and it has been found to be involved in higher cognitive tasks, possessing a functional topography in relation to specific cognitive functional categories (Tomasino and Gremese 2016). Indeed, the involvement of M1 in cognitive processing has been suggested by TMS studies, which showed an effect of motor cortex regarding: executive functioning and working memory, language, visual attention, and semantic memory (Tomasino et al 2011;Miranda 2013;Lattari et al 2017;Morya et al 2019). Recently, a bi-directional change in excitability from the stimulated DLPFC to M1 has been observed in healthy humans (Cao et al 2018) and rTMS studies have demonstrated that the stimulation of M1 can be modulated by prior stimulation of other cerebral areas, such as the ipsilateral DLPFC (Mastropasqua et al 2014).…”
Section: Introductionmentioning
confidence: 99%